Towards a patient-centred understanding of engagement in medical care among adults diagnosed with HIV in South Africa - Mabuto, Tonderai (My University, 2020)
Background: The availability of simple and well-tolerated antiretroviral therapy (ART) makes early initiation of lifelong HIV treatment practical and safe. However, attempts to identify pragmatic and effective strategies to overcome challenges to early and sustained engagement in HIV medical care in sub-Saharan Africa have yielded limited success. Understanding HIV medical care-seeking behaviour has become an increasingly important area of research, as guidelines and national policies throughout the world are calling for universal access to ART with rapid initiation of therapy after diagnosis. Methods: This thesis draws upon five studies to identify the contextual factors that influence patient-level decisions for engagement in HIV medical care among adults diagnosed with HIV and to explore how each of the identified factors plays a role in shaping healthcare-seeking decisions. The first study is a quantitative analysis of factors associated with linkage-to-care within 180 days of receiving an HIV diagnosis, among ART-eligible participants diagnosed through community-based mobile HIV testing services (HTS). The second study explores how contextual factors influence the way ART-eligible individuals ascribe meaning to their HIV diagnosis and their perceptions on the value of HIV medical care. The third study is based on in-depth longitudinal interviews to explore how perceptions of clinic-level costs, influence engagement in HIV medical care. The last two studies examine the content and delivery of interpersonal health communication within the context of a pragmatic randomised trial and routine clinic settings. I apply regression techniques for quantitative data and thematic approaches to qualitative data analysis to address my thesis objectives. Results: This doctoral research adds to the existing literature on linkage-to-care by contextualising individual-level healthcare-seeking decisions within a structured framework that brings together explanatory behaviour models and social-ecological levels. From the quantitative analyses, I learnt that just over half of the participants who knew their eligibility to initiate ART when they were diagnosed, engaged in HIV medical care within the first 180 days of receiving their diagnosis. I identified disclosure of HIV status as a facilitator for linkage-to care, a greater effect of disclosure on linkage-to-care for men than women. Study findings also highlighted the additional role of repeat HIV testing as a tool for facilitating linkage-to care among PLHIV aware of their status, who had not engaged in care. On the contrary, being in a relationship was a risk factor for failure to enter care within 180 days of receiving an HIV diagnosis. Our qualitative work further revealed how the ‘processing’ of the HIV diagnosis and perceptions of the value placed on ART, are still essential factors even among individuals who qualify for ART. From a value-cost perspective, I learnt that the way HIV medical care services are delivered in public sector clinics can escalate the costs of linkage-to-care and shift the balance further away from care engagement. Worryingly, this also affected people motivated to engage in HIV medical care. Also, our study findings suggest that structured approaches to longitudinal case management support have the potential to improve linkage-to-care. Yet, our review of transcripts of post-test counselling sessions for HIV-positive clients in public sector clinics creates a concerning picture as the content and delivery of post-test counselling falls short of promoting the current goals of universal test and treat. Conclusion: There is an urgent need to reengineer HIV medical care delivery towards patient-centred approaches which promote the value PLHIV place of medical care while identifying pragmatic approaches to reduce the costs of engaging in medical care. Without addressing costs and assuring perceptions of the value of clinical care, the number of people engaging in HIV medical care is likely to fall short of the 90-90-90 goals
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2020